The Concept of Effective Porosity in the Discharge Rate Performance of High-Density Positive Electrodes for Automotive Application. Issue 16 (25th November 2020) - Tambio, S. J.; Cadiou, F.; Maire, E.; Besnard, N.; Deschamps, M.; Lestriez, B.
Abstract : The discharge rate performance of NMC532-based electrodes designed for EV application were measured between 0 °C and 40 °C and were compared to the predictions of the electrolyte limited penetration depth model [Gallagher et al., J. Electrochem. Soc. 163, A138 (2016)], also called diffusion limited current density model [Heubner et al., J. Power Sources 419, 119 (2019)]. To support this analysis, we took into account the actual microstructure of the electrodes, previously characterized by FIB/SEM tomography, and their measured and/or simulated transport properties. We show that the performance of NMC532 electrodes, even with a low carbon content below the percolation threshold, are not limited by electrons transport through the electrode due to the high intrinsic conductivity of this active material. At 40 °C, the swelling of the PVdF by the electrolyte solvents penalizes performance, especially as the binder content is high. Above all, the current density at which a brutal decrease in capacity occurs is well predicted by the model, although by reducing the porosity to its percolated micrometer sized fraction. This is in good agreement with the numerical simulations of the ionic transport properties.